CRITICAL THINKING: A FUNDAMENTAL SKILL FOR MODERN LIFE - Sultonova Maftuna Bakhtiyorovna (Journals Park Publishing, 2024)
Critical thinking is an essential cognitive process for evaluating information and arguments, crucial for informed decision-making in personal and professional contexts. This article explores the definition, importance, and development of critical thinking skills, emphasizing its role in enhancing problem-solving, fostering creativity, and promoting rationality.
Keywords: Critical thinking, cognitive skills, decision-making, problem-solving, rationality, creativity, evidence evaluation, communication, academic success, workplace efficiency.